In Silico Molecular Modeling and Docking Studies on the Leishmanial Tryparedoxin Peroxidase - (:unkn) unknown (INST TECNOLOGIA PARANA, 2014)
Leishmaniasis is one of the most common form of neglected parasitic disease that affects about 350 million people worldwide. Leishmanias have a trypanothione mediated hydroperoxide metabolism to eliminate endogenous or exogenous oxidative agents. Both of 2-Cys peroxiredoxin (Prx) and glutathione peroxidase type tryparedoxin peroxidase (Px) are the terminal enzymes in the trypanothione dependent detoxification system. Therefore absence of trypanothione redox system in mammals and the sensitivity of trypanosomatids against oxidative stress, enzymes of this pathway are drug targets candidates. In this study, 3D structure of tryparedoxin peroxidase (2-Cys peroxiredoxin type) from Leishmania donovani (LdTXNPx) was described by homology modeling method based on the template of tryparedoxin peroxidase from Crithidia fasciculata and selected compounds were docked to the active site pocket. The quality of the 3D structure of the model was confirmed by various web based validation programs. When compared secondary and tertiary structure of the model, it showed a typical thioredoxin fold containing a central beta-sheet and three alpha-helices. Docking study showed that the selected compound 2 (CID 16073813) interacted with the active site amino acids and binding energy was -118.675 kcal/mol.
Keywords: Homology modeling; docking; Leishmania donovani; tryparedoxin peroxidase; hydroperoxide metabolism; TRYPANOTHIONE REDUCTASE; TRYPANOSOMA-CRUZI; CRYSTAL-STRUCTURE; 2-CYS PEROXIREDOXIN; OXIDATIVE STRESS; DRUG TARGETS; METABOLISM; MITOCHONDRIAL; PROTEINS; ENZYMES